Entrepreneurship Training and Assistance in Processing Healthy Vegetable Chips for Residents of Duwet Village, Kec. Tumpang, Kab. Malang - Lestari, Baroroh; Widiyowati, Eny; Suryanto, Bambang; Himma, Mahmudatul; Wahyu, Ellyn Eka; Senja O., Yekie (Transpublika Publisher, 2024)
One of the main sources of income in Duwet Village, Tumpang District, Malang Regency is the agricultural sector. Agricultural products that are processed properly will be one of the strategies that can be done to increase the selling value of the product. One of them is by making vegetables as chips. The main focus of this service is making chips made from vegetables. With the training provided, it is intended that the community can make their own various preparations from vegetables that can be served as snacks for the family. In addition, it can also be used to open business opportunities to increase income by utilizing ingredients available in nature. The implementation of the service was carried out in the form of a presentation, followed by a direct demonstration of the process of making vegetable chips. Evaluation of activities is carried out by collecting and summarizing data obtained through filling out questionnaires given to training participants. In this service activity, 4 experiments were carried out so that the results of crispy chips were obtained and did not change the taste of the vegetables used as chips. In addition, training and assistance in the process of making vegetable chips was also carried out by the service team. Based on the results in the field, it was found that the process of making chips was quite easy. Further training is needed for packaging and marketing so that the products produced can be better known to the public.